2005
DOI: 10.1007/s00221-005-0191-y
|View full text |Cite
|
Sign up to set email alerts
|

Face-selective and auditory neurons in the primate orbitofrontal cortex

Abstract: Neurons with responses selective for faces are described in the macaque orbitofrontal cortex. The neurons typically respond 2-13 times more to the best face than to the best non-face stimulus, and have response latencies which are typically in the range of 130-220 ms. Some of these face-selective neurons respond to identity, and others to facial expression. Some of the neurons do not have different responses to different views of a face, which is a useful property of neurons responding to face identity. Other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 73 publications
8
69
0
Order By: Relevance
“…The pattern of activity in this region seen here, and for validly cued versus invalidly cued angry probes, is consistent with work demonstrating a role for the orbitofrontal cortex and adjacent prefrontal areas in social and emotional responses to faces (Rolls, Critchley, Browning, & Inoue, 2006; Wilson, O'Scalaidhe, & Goldman-Rackic, 1993). These areas are not only implicated in decoding the social information and social reinforcement conveyed in emotional expressions but also in using this information to guide social interactions (for review see Rolls, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…The pattern of activity in this region seen here, and for validly cued versus invalidly cued angry probes, is consistent with work demonstrating a role for the orbitofrontal cortex and adjacent prefrontal areas in social and emotional responses to faces (Rolls, Critchley, Browning, & Inoue, 2006; Wilson, O'Scalaidhe, & Goldman-Rackic, 1993). These areas are not only implicated in decoding the social information and social reinforcement conveyed in emotional expressions but also in using this information to guide social interactions (for review see Rolls, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…Anatomically, there does not appear to be a whole further set of visual processing areas present in the brain; and outputs from the temporal lobe visual areas such as those described, are taken to limbic and related regions such as the amygdala and orbitofrontal cortex, and via the entorhinal cortex to the hippocampus, where associations between the visual stimuli and other sensory representations are formed Rolls 2005). Indeed, tracing this pathway onward, we have found a population of neurons with face-selective responses in the amygdala Rolls 2000b) and orbitofrontal cortex (Rolls et al 2006a), and in the majority of these neurons, different responses occur to different faces, with ensemble (not local) coding still being present. The amygdala in turn projects to another structure that may be important in other behavioral responses to faces, the ventral striatum, and comparable neurons have also been found in the ventral striatum (Williams et al 1993).…”
Section: Y2mentioning
confidence: 69%
“…In humans, bilateral dysfunction of the amygdala can impair face expression identifi cation, although primarily of fear (Adolphs et al 1995;Adolphs et al 2002), so that the impairment seems much less severe than that produced by orbitofrontal cortex damage. Rolls et al (2006a) have found a number of face-responsive neurons in the orbitofrontal cortex, and they are also present in adjacent prefrontal cortical areas (Wilson et al 1993). The orbitofrontal cortex face-responsive neurons, fi rst observed by Thorpe et al (1983), then by Rolls et al (2006a), tend to respond with longer latencies than temporal lobe neurons (140-200 ms typically, compared with 80-100 ms); they also convey information about which face is being seen, by having different responses to different faces (Fig.…”
Section: A Representation Of Faces In the Amygdalamentioning
confidence: 99%
See 2 more Smart Citations